1, 4‐Dioxane Treatment Technologies. Issue 1 (5th December 2016) - DiGuiseppi, William; Walecka‐Hutchison, Claudia; Hatton, Jim
Abstract : The chlorinated solvent stabilizer 1, 4‐dioxane (DX) has become an unexpected and recalcitrant groundwater contaminant at many sites across the United States. Chemical characteristics of DX, such as miscibility and low sorption potential, enable it to migrate at least as far as the chlorinated solvent from which it often originates. This mobility and recalcitrance has challenged remediation professionals to redesign existing treatment systems and monitoring networks to accommodate widespread contamination. Furthermore, remediation technologies commonly applied to chlorinated solvent co‐contaminants, such as extraction and air stripping or in situ enhanced reductive dechlorination, are relatively ineffective on DX removal. These difficulties in treatment have required the industry to identify, develop, and demonstrate new and innovative technologies and approaches for both ex situ and in situ treatment of this emerging contaminant. Great strides have been made over the past decade in the development and testing of remediation technologies for removal or destruction of DX in groundwater. This article briefly summarizes the fate and transport characteristics of DX that make it difficult to treat, and presents technologies that have been demonstrated to be applicable to groundwater treatment at the field scale.  ©2016 Wiley Periodicals, Inc.